Answer:
Explanation:
Find the variable in the expression and see what has been done to it. Here, 'a' has been multiplied by c, and b has been subtracted from the product. Undo those operations in reverse order.
Undo the subtraction of b by adding b to both sides.
g +b = ca -b +b
g +b = ca . . . . . note b is no longer subtracted from the product
Undo the multiplication by dividing both sides by c.
(g +b)/c = (ca)/c
(g +b)/c = a
a = (g +b)/c
__
The second problem is worked exactly the same way.
u = 2x -2
u +2 = 2x . . . . . add 2 to both sides
(u +2)/2 = x . . . . divide both sides by 2
x = (u +2)/2